2021
DOI: 10.3389/fmicb.2021.744733
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Genera Colonization of Ocimum tenuiflorum Endophytes in Tomato and Their Complementary Effects on Na+/K+ Balance, Oxidative Stress Regulation, and Root Architecture Under Elevated Soil Salinity

Abstract: Endophytic bacilli of ethano-botanical plant Ocimum tenuiflorum were screened for salt stress-alleviating traits in tomato. Four promising O. tenuiflorum endophytes (Bacillus safensis BTL5, Bacillus haynesii GTR8, Bacillus paralicheniformis GTR11, and Bacillus altitudinis GTS16) were used in this study. Confocal scanning laser microscopic studies revealed the inter-genera colonization of O. tenuiflorum endophytes in tomato plants, giving insights for widening the applicability of potential endophytes to other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 93 publications
5
35
0
Order By: Relevance
“…Endophytes have been reported to maintain ROS homeostasis in both biotic ( 2020 ; Sahu et al., 2019 ; Singh et al., 2020 ) and abiotic stresses ( Sahu et al., 2021 ). Endophytes decrease ROS content in the plant cells by increasing scavenging via increased redox state of glutathione and ascorbate along with promoting antioxidant enzyme activities ( Sadeghi et al., 2020 ).…”
Section: Role Of Endophytes In Ros Homeostasismentioning
confidence: 99%
“…Endophytes have been reported to maintain ROS homeostasis in both biotic ( 2020 ; Sahu et al., 2019 ; Singh et al., 2020 ) and abiotic stresses ( Sahu et al., 2021 ). Endophytes decrease ROS content in the plant cells by increasing scavenging via increased redox state of glutathione and ascorbate along with promoting antioxidant enzyme activities ( Sadeghi et al., 2020 ).…”
Section: Role Of Endophytes In Ros Homeostasismentioning
confidence: 99%
“…We found that the ratio of Na + (root) to Na + (leaf) markedly decreased in un-inoculated bermudagrass compared with E. ludwigii B30 inoculated bermudagrass under SS, indicating that E. ludwigii B30 inoculation restricted Na + translocation from the roots to aerial parts of bermudagrass, thereby restricting toxic Na + accumulation within photosynthetic tissues ( Porcel et al, 2016 ). Sahu et al (2021) showed similarly that endophytic bacteria inoculation restricted Na + translocation from the roots to shoot in salt-stressed tomato. Under SS, excess Na + ions will compete against K + (the other macronutrient), inducing nutritional and metabolic disturbance and exerting adverse impacts on plants.…”
Section: Discussionmentioning
confidence: 84%
“…In recent years, researchers have been trying to explore the evolutionary relationship between host and endophytes, and trace the reciprocity mechanism of this specific evolutionary relationship, in order to provide theoretical basis for the commercial development of endophytes. At present, some endophytic bacteria and their active products have been successfully used in commercial production and obtained great benefits in the preparation of new drugs and agricultural protection ( Singh and Gaur, 2017 ; Mishra et al, 2018b ; Sahu et al, 2021 ). It is of great economic value to reveal the interactive mechanisms between plants and endophytes to explore and release the potential for the industrial development of endophytes.…”
Section: Introductionmentioning
confidence: 99%